Culinary Tourism in Kutawaringin (Bandung): Structural Relationship Between Food Quality, Tourist Perceptions, And Culinary Tourism Satisfaction - Annisa Bintang Kusumawardhani; Awaludin Nugraha; Evi Novianti (Politeknik Pariwisata Makassar, Indonesia, 2024)
This study assessed tourist satisfaction with culinary tourism in Kutawaringin District, Bandung Regency. A quantitative descriptive approach was used to reveal tourist perceptions and the impact of food quality on culinary tourism satisfaction in Kutawaringin District, Bandung Regency. Data was collected through interviews, observation, and documentation. A random sample of tourists completed the questionnaire. The study sample consisted of 50 individuals who participated in in-depth interviews. It is important to note that these evaluations are based solely on objective criteria and do not include subjective opinions. Lemon tea was found to be the most popular food item, while tourists rated the seller's service highest at 74%. Food hygiene received a rating of 71%; food tastes 60%; affordability of the seller's location 57%; food quality and promotion 46%; and food prices 40%, all with a fair assessment. Collaboration is necessary among tourism managers and stakeholders to make Kutawaringin a supporting factor for the Bandung Destination. This requires consideration of various factors, including food prices, packaging quality, and promotion